The Revolutionary Left Movement according to the CIA - Téllez Lúgaro, Eduardo; Novoa Saldías, Felipe; Iturra Fonseca, Nicolás (Cuadernos de Historia, 2023)
The document that is published corresponds to an evaluation carried out by the Central Intelligence Agency (CIA), at the beginning of the government of Salvador Allende and the Popular Unity (19701973), regarding the Revolutionary Left Movement (MIR), the main reference of the Chilean extreme left. Said report allows us to have a close perspective of the points of view and background that the CIA held about this revolutionary organization, including its historical trajectory and close relationship with the Cuban government before and during the experience of the Popular Unity.